北冰洋楚科奇海浮游细菌丰度和生产力及其分布特征 - 高源; 何剑锋; 陈敏; 林凌; 张芳 (2015)
2012年夏季中国第5次北极科学考察期间,对北冰洋楚科奇海及其北部边缘海浮游细菌丰度和生产力进行了测定,并将其与环境因子进行了相关性分析。结果显示,楚科奇海浮游细菌丰度的变化范围为0.56x108~6.41x108 CEllS/dM3,平均为2.25x108 CEllS/dM3;细菌生产力介于0.042~1.92Mg/(M3·d)(以碳计)之间,平均为0.54Mg/(M3·d)(以碳计),与已有研究结果基本相当。陆架区细菌丰度和生产力要明显高于北部边缘区,但前者的单位细菌生产力则较低。与环境因子的相关性分析显示,细菌丰度与温度和叶绿素A浓度存在显著正相关(P<0.01),表明北极变暖导致的海水升温及浮游植物生物量的增加均会促进细菌的生长,从而进一步提高细菌在海洋生态系统和碳循环中的作用。但陆架区的细菌生产力与环境参数均没有显著相关性,表明其影响因素较为复杂;生产力在北部边缘区则仅与叶绿素A存在显著正相关(P<0.01),表明浮游植物生长过程产生的溶解有机碳(dOC)是细菌生长最为主要的碳源,碳源的单一可能制约细菌的生产从而导致该海域无冰状态下细菌丰度的增加不如预期,但融冰过程带来的大量dOC将促进细菌活性的增加。 The abundance and production of bacterioplankton with their correlations with environmental factors were investigated in the Chukchi Sea and its northern border areas in 2012 summer.The abundances of bacterioplankton in and near the Chukchi Sea range from 0.56×108 to 6.41×108 cells/dm3,with an average of 2.25×108 cells/dm3.Bacterial productions are between 0.042mg/(m3·d)(in carbon)and 1.92mg/(m3·d)(in carbon),with an average of 0.54mg/(m3·d)(in carbon).These results are similar with previous studies in the Arctic Ocean.In the shelf region,the abundances and productions of bacteria are obviously higher than those in the northern border areas,but the specific bacterial production is lower.The environmental correlation analysis shows that bacterial abundance is positively correlation with temperature and Chl aconcentration(p<0.01),indicating that both the increase of water temperature and phytoplankton biomass will enhance the growth of bacterioplankton in the Chukchi Sea which will further promote the role of bacteria in the marine ecosystem and carbon cycle.On the contrary,bacterial production has no correlation with environmental factors in the shelf region,but shows a significant positive correlation with Chl ain northern border area(p<0.01),suggesting that the growth of bacteria mainly depends on DOC released by phytoplankton in border area.The simplicity of carbon source may restrict the productivity of bacteria in the northern border area,and the DOC released from melting ice will stimulate the bacterial activity. 国家自然科学基金(41476168;41206189); 南北极环境考察与评估专项(CHINARE2011-2015); 海洋公益专项(201105022)